2010
DOI: 10.1086/651144
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Reactive Neutralizing Humoral Immunity Does Not Protect from HIV Type 1 Disease Progression

Abstract: Broadly reactive neutralizing antibodies are the focus of human immunodeficiency virus (HIV) type 1 vaccine design. However, only little is known about their role in acquired immunodeficiency syndrome (AIDS) pathogenesis and the factors associated with their development. Here we used a multisubtype panel of 23 HIV-1 variants to determine the prevalence of cross-reactive neutralizing activity in serum samples obtained approximately 35 months after seroconversion from 82 HIV-1 subtype B-infected participants fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
175
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(199 citation statements)
references
References 46 publications
19
175
4
1
Order By: Relevance
“…However, R166, D167, and K168 are very well conserved across subtypes A, B, and C. The existence of subtype-specific epitopes is borne out by existing MAbs-2G12 and 2F5 fail to neutralize most subtype C viruses because of genetic variability in the epitope, and IgG1b12 neutralizes two-thirds of subtype B and C viruses but only a third of subtype A viruses (2). Preferential neutralization by polyclonal plasma of subtype-matched heterologous viruses has also been shown by us (32) and others (1,3,8,38,41). Indeed, within the CAPRISA cohort, all of whose members were infected with subtype C viruses, we note significantly better neutralization of subtype C than of subtype B viruses (data not shown).…”
Section: Discussionmentioning
confidence: 80%
“…However, R166, D167, and K168 are very well conserved across subtypes A, B, and C. The existence of subtype-specific epitopes is borne out by existing MAbs-2G12 and 2F5 fail to neutralize most subtype C viruses because of genetic variability in the epitope, and IgG1b12 neutralizes two-thirds of subtype B and C viruses but only a third of subtype A viruses (2). Preferential neutralization by polyclonal plasma of subtype-matched heterologous viruses has also been shown by us (32) and others (1,3,8,38,41). Indeed, within the CAPRISA cohort, all of whose members were infected with subtype C viruses, we note significantly better neutralization of subtype C than of subtype B viruses (data not shown).…”
Section: Discussionmentioning
confidence: 80%
“…The development of neutralization breadth does not appear to impact the progression of HIV‐1 disease48, 67; for example, many individuals in these longitudinal cohorts went on antiretroviral therapy as part of standard of care during the course of study,48, 50 including those with high degrees of breadth 48. Examination of viruses and antibodies taken from the same HIV‐1‐infected individuals has consistently shown that circulating bnAbs cause extinction of susceptible virus populations despite ongoing viremia,23, 24, 25 although viruses susceptible to less potent neutralizing antibodies continue to circulate 25.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 99%
“…However, because some HIV-1-infected individuals can develop bnAbs over the course of infection, these various evasion strategies are not insurmountable (1,(25)(26)(27). Although bnAbs do not seem to confer significant protection against disease progression in infected individuals (28,29), their induction through vaccination might prevent the acquisition of infection. Thus, the epitopes recognized by bnAbs are now being carefully scrutinized to serve as templates for rational vaccine design.…”
mentioning
confidence: 99%